2008
DOI: 10.1116/1.2894895
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled nanotube polymer composite degradation under high emission current regime as revealed by mass spectrometry

Abstract: Local current mapping of single vertically aligned multi-walled carbon nanotube in a polymer matrix J. Appl. Phys. 112, 084327 (2012); 10.1063/1.4759349 High emission currents and low threshold fields in multi-wall carbon nanotube-polymer composites in the vertical configuration J. Appl. Phys. 111, 044307 (2012); 10.1063/1.3685754Temperature evaluation of field emitting points for polymer-carbon nanotube composite using time-of-flight mass spectrometry J.In this work the authors study field-emission properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…In the corresponding partial spectrum a small amount of CO and CO2 is also observed. In earlier work [8] in the conditions of high currents of the field emission the kinetics of intensive release of CO and CO 2 is observed for cathode and anode correspondently.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the corresponding partial spectrum a small amount of CO and CO2 is also observed. In earlier work [8] in the conditions of high currents of the field emission the kinetics of intensive release of CO and CO 2 is observed for cathode and anode correspondently.…”
Section: Introductionmentioning
confidence: 79%
“…The procedure of manufacturing of an emitting surface of the cathode is featured in [8]. Here we also preferentially used MWCNT-polystyrene emitter which not only shows high levels of an emission current, but also serves as the modeling sample for an estimate of temperature near to emission centers in polymeric matrix [10].…”
Section: Experimental Technique and The Emittermentioning
confidence: 99%
See 1 more Smart Citation
“…21,35,36 Similar yields ͓ ϳ͑0.5-1.3͒ ϫ 10 −1 CO x / O͔ have been observed for hyperthermal ͑ϳ5 eV͒ neutral O impinging the basal plane of pyrolytic graphite at room temperature. 37,38 Popov et al 39 observed a similar crossover in field emission testing of CNTs in polymer composites in a parallel plate configuration; however, they attributed the signal entirely to ESDgenerated products at the anode. Alternatively, calculations have shown that CO incident with O on graphite can result in CO 2 production.…”
Section: Hyperthermal Atom Reactions With Atomic Oxygenmentioning
confidence: 92%
“…Initially, the CO was the dominant ESD species but eventually, the CO 2 became dominant. 39 The CO-CO 2 crossover observed may be because the chemical erosion increases the defect density in the film and the probability of oxygen adsorption. Pristine, as-grown CNS ͑as measured by Auger electron spectroscopy͒ does not adsorb oxygen, but graphene films with a significant defect density will adsorb oxygen.…”
Section: Hyperthermal Atom Reactions With Atomic Oxygenmentioning
confidence: 98%